The histology and cytology of changes in the epithelium of the cervix uteri - Govan, A. D. T. (1969)
Abnormalities of the cervical epithelium are set out in two main groups: bland lesions which are regarded as unrelated to malignancy, and malign lesions which are considered as potential precursors of invasive carcinoma. The histological features of each condition and the cytological pattern of the corresponding cervical smear are described and correlated. Cone biopsy is advocated as the only satisfactory form of cervical biopsy for both the diagnosis and evaluation of lesions such as dysplasia and carcinoma in situ. It is emphasized that further study is necessary to determine their natural history and prognosis in relation to invasive carcinoma.